A modeling and distributed MPC approach for water distribution networks. (December 2018) - Berkel, Felix; Caba, Sebastian; Bleich, Jonas; Liu, Steven
Abstract: This paper deals with the modeling and control of water distribution networks consisting of multiple pressure zones that are interconnected by fixed-speed pumps. A simplified control-oriented model with linear dynamics and non-convex constraints which considers the pressures and losses in the zones is derived. Based on the model, a periodic distributed model predictive scheme which is tailored to the non-convex constraints and minimizes an economic objective is introduced. The scheme uses event-triggered communication between the subsystems to reduce the communicational load. The proposed model and controller are evaluated using a model of the water distribution network of the city of Kaiserslautern, Germany.